Two Cases of Ischemic Complications in Abdominoplasty After Use of a New Biologic Migraine Medication - Reetta Tuominen, MD, PhD; Virve Koljonen, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Abdominoplasty is a common aesthetic procedure, and ischemic complications are rare, particularly in nonsmokers. We present 2 cases of ischemic complications in nonsmoking patients treated with fremanezumab, a biologic medication for severe migraines. A 55-year-old woman underwent lipoabdominoplasty on December 18, 2023. At the 16-day postoperative follow-up, demarcated necrosis was observed beneath the wound tape, and secondary direct closure was performed 6 weeks later. She had been using fremanezumab for 4 years. A 47-year-old woman underwent abdominoplasty on April 23, 2024, with moderate dissection and liposuction to the flanks. Signs of abdominal flap ischemia were evident in the operating room, and treatment for the Raynaud phenomenon was initiated immediately. The ischemia demarcated over 2 weeks, and secondary direct closure was performed 3 weeks postoperatively. She had been using fremanezumab for two months. Calcitonin gene-related peptide antagonists are potent medications for severe migraine with few contraindications. Fremanezumab may affect peripheral circulation, potentially increasing the risk of surgical complications.